Enhanced biological activity of liposomal methylated resveratrol analog 3'-hydroxy-3,4,5,4'-tetramethoxystilbene (DMU-214) in 3D patient-derived ovarian cancer model - Andrzej Nowicki; Dariusz Wawrzyniak; Mikołaj Czajkowski; Małgorzata Józkowiak; Michał Pawlak; Marcin Wierzchowski; Katarzyna Rolle; Paulina Skupin-Mrugalska; Hanna Piotrowska-Kempisty (Taylor & Francis Group, 2022)
3'-hydroxy-3,4,5,4'-tetramethoxystilbene (DMU-214) belongs to methoxystilbenes family and is an active metabolite of 3,4,5,4'-tetramethoxystilbene (DMU-212). In several of our previous studies, the anti-apoptotic activity of DMU-214 was significantly higher than that of the parent compound, especially in ovarian cancer cells. Due to increased lipophilicity and limited solubility, methoxystilbenes require a solubilization strategy enabling DMU-214 administration to the aqueous environment. In this study, DMU-214-loaded liposomes were developed for the first time, and its antitumor activity was tested in the ovarian cancer model.First, several liposomal formulations of DMU-214 were obtained by the thin lipid film hydration method followed by extrusion and then characterized. The diameter of the resulting vesicles was in the range of 118.0-155.5 nm, and samples presented monodisperse size distribution. The release of DMU-214 from the studied liposomes was governed by the contribution of two mechanisms, Fickian diffusion and liposome relaxation.Subsequently, in vitro activity of DMU-214 in the form of a free compound or liposome-bound was studied, including commercial cell line SK-OV-3 and patient-derived ovarian cancer cells in monolayer and spheroid cell culture models. DMU-214 liposomal formulations were found to be more potent (had lower IC50 values) than the free DMU-214 both in the monolayer and, more significantly, in both examined spheroid models. The above results, with particular emphasis on the patient-derived ovarian cancer model, indicate the importance of further development of liposomal DMU-214 as a potential anticancer formulation for ovarian cancer treatment.